1, 1-Difluoroethane Forensic Aspects for the Toxicologist and Pathologist. Issue 8 (21st May 2021) - Tiscione, Nicholas B; Rohrig, Timothy P
Abstract: 1, 1-Difluoroethane (DFE) is a halogenated hydrocarbon that is commonly used as a propellant in air duster products. Herein, the pharmacology of DFE was reviewed, and questions relevant to medicolegal investigations were addressed. Particular emphasis was given to detection time in biological specimens and the range, onset and duration of effects. DFE may be abused as an inhalant and is rapidly absorbed through the lungs. Onset of central nervous system (CNS) depressant effects is within seconds and the duration may only last minutes. The effects may lead to impairment of human performance, including confusion, lethargy, impaired judgment, loss of motor coordination and loss of consciousness. Death may result even after the first use. With heavy use or in combination with other CNS depressants, extended periods of drowsiness or loss of consciousness may be observed with an increased risk of a fatal event. A majority of impaired driving investigations where DFE was identified included a collision demonstrating the significant impact its use may have on traffic safety. When DFE is identified alone, without other drugs that cause CNS impairment, the effects may not be observable minutes after the crash, making identification of its use difficult. Although concentrations dissipate rapidly, DFE has been detected in blood specimens collected up to 3 hours after the driving incident. Two studies on passive exposure presented herein demonstrated that it is unlikely to detect DFE above concentrations of ∼2.6 µg/mL in blood or urine due to even extreme unintentional exposure. Alternative specimens such as brain, lung and tracheal air should be considered in some postmortem investigations. DFE has been identified in blood specimens from postmortem cases at concentrations from 0.14 to 460 µg/mL and in impaired driving cases from 0.16 to 140 µg/mL.